Pengaruh Disiplin dan Motivasi Kerja terhadap Kinerja Guru SMA Swasta Se-Kecamatan Baturaja Timur - Ery Masni Pane; Tri Widayatsih; Emawati Emawati (Departement of Mathematics Education, 2023)
This study aims to identify and describe: 1). the effect of discipline on teacher performance; 2) the effect of work motivation on teacher performance, 3) the effect of discipline and work motivation on the performance of teachers in private high schools throughout East Baturaja District. This study uses a quantitative descriptive method. The population and sample in this study were 55 teachers in private high schools in East Baturaja District, with the sample technique used was proportionate stratified random sampling. The data collection technique used is a questionnaire. Data were analyzed using simple linear and multiple linear regression formulas using the SPSS (Statistical Product and Services Solution) program. The results of the study show that: 1) There is a significant influence of discipline on the performance of private high school teachers in East Baturaja District; 2) There is a significant influence of work motivation on the performance of private high school teachers in East Baturaja District; 3) There is a significant influence of discipline and work motivation on the performance of private high school teachers in East Baturaja District. This can be seen from the results of the F test which shows a significance value of 0.000 <0.005. The influence of discipline and work motivation together on teacher performance is 43.2%, the remaining 56.8% is influenced by other factors.